The lion's grave dispatches from Afghanistan - Anderson, Jon Lee 1957- (Grove Press, 2002)
Two weeks after the terrorist attacks of September 11, correspondent and bestselling author Anderson became one of the first Western journalists to get into Afghanistan. Distinguished by his gritty, on-the-ground observations, probing interviews, and gift for telling a story, The Lion's Grave is war reporting in the tradition of A.J. Liebling and Michael Herr.
Map of Afghanistan on lining papers.
Keywords: Anderson, Jon Lee; Geschichte; Afghanistan -- History -- 2001-